Syntheses, characterization, crystal structures and Jack bean urease inhibitory activities of ZnII, CoII/III and NiII complexes derived from reduced Schiff base ligand. (1st July 2019) - Li, Yanmin; Xu, Luyao; Duan, Mengmeng; Zhang, Bitong; Wang, Yinghui; Guan, Yixing; Wu, Jiahui; Jing, Changling; You, Zhonglu
Graphical abstract: A series of new Zn II, Co II/III and Ni II complexes derived from reduced Schiff base were prepared and characterized. The cobalt complex and the nickel complex have effective urease inhibitory activities. Molecular docking study of the complexes was studied. Abstract: A series of new Zn II, Co II/III and Ni II complexes derived from reduced Schiff base 6, 6′-((propane-1, 3-diylbis(azanediyl))bis(methylene))bis(2-ethoxyphenol) (H2 L), [Zn3 L2 (N3 )2 ] (1 ), [Co2 L(N3 )2 (CH3 COO)]·CH3 OH (2 ) and [Ni(HL)(OH2 )(CH3 OH)]·ClO4 (3 ), were prepared and characterized by physico-chemical methods. Crystal structures of the complexes were determined by single crystal X-ray diffraction. Complex1 is a trinuclear zinc(II) compound. Complex2 is a dinuclear cobalt(II/III) compound. Complex3 is a mononuclear nickel(II) compound. The cobalt complex and the nickel complex have effective urease inhibitory activities, with IC50 values of 19.8 and 11.6 μmol·L −1, respectively. However, the zinc complex1 has no such activity. Molecular docking study of complexes2 and3 with the active center of Jack bean urease was studied.